Thermodynamic and Kinetic Considerations Regarding the Prospects for a Dual-Purpose Hydrogen Extraction and Separation Membrane - Karl Sohlberg (Energies, 2021)
Extraction of hydrogen from hydrocarbons is a logical intermediate-term solution for the escalating worldwide demand for hydrogen. This work explores the possibility of using a single membrane to accomplish both the catalytic dehydrogenation and physical separation of hydrogen gas as a possible way to improve the efficiency of hydrogen production from hydrocarbon sources. The present analysis shows that regions of pressure/temperature space exist for which the overall process is thermodynamically spontaneous (ΔG < 0). Each step in the process is based on known physics. The rate of hydrogen production is likely to be controlled by the barrier to hydrogen abstraction, with the density of H-binding sites also playing a role. A critical materials issue will be the strength of the oxide/metal interface.